Methodology to facilitate successful lean implementation - Berlec, Tomaž (Strojniški vestnik, 2017)
The implementation of lean production in a company is a transformation of the whole company's culture. To achieve such a lean culture, the role and support of management are decisive. This paper introduces a newly defined model and methodology with an interview guide which helps to distinguish a supportive from a non-supportive management team when introducing lean production, and helps to decide if a step needs to be repeated, improved, or the next step can be initiated. The methodology is especially suitable for small and medium-sized enterprises (SME's), because of their lack of human resources, where this model was also tested.
Keywords: interview; intervju; kritični faktorji uspeha; kultura podjetja; učenje managementa; vitka proizvodnja